Gait dynamics and brain function abnormalities in Parkinson’s disease with freezing of gait: a clinical study using resting-state fMRI and wearable devices - Xiaohong Li; Mengdi Hou; Yan Qu; Yuan Huo; Shuting Liu; Minghui Ma; Zhanhua Liang (Frontiers in Neuroscience)
IntroductionParkinson’s disease (PD)-associated freezing of gait (FoG) (PDFoG) refers to episodes where patients feel the urge to move but experience temporary immobility or markedly shortened steps. This leads to frequent falls and, eventually, the loss of walking ability, severely affecting patient quality of life and life expectancy. Despite its clinical importance, the neural mechanisms underlying PDFoG remain unclear.MethodsThis study sought to characterize abnormal neural activity in PDFoG by assessing regional brain activity using ALFF, fALFF, PerAF, and wavelet-ALFF across three frequency bands (conventional, slow-5, and slow-4). PDFoG patients were compared to PD patients without FoG (PDnFoG) and healthy controls. Clinical evaluations included standard assessment scales, such as the FOG-Q and MDS-UPDRS III, alongside a wearable sensor-based gait assessment system.ResultsWe found that PD patients with FoG experienced more extensive changes in regional brain activity than those without FoG, primarily affecting cortical regions and the cerebellum. Conversely, PDnFoG patients primarily showed reduced activity in the basal ganglia.ConclusionThese findings emphasize the need to further explore the roles of the cerebral cortex and cerebellum in PDFoG pathophysiology.